Identification of the key role of IL-17RB in the treatment of osteoarthritis with Shaoyao Gancao decoction: Verification based on RNA-seq and bioinformatics analysis - Chengzhi Hou; Zhangjingze Yu; Qinghui Song; Xuelei Chu; Guangcheng Wei; Jia Zhu; Liping Yang; Yong Zhao; Ping Zhang; Qiuyue Li (PLoS ONE, 2025)
Background Shaoyao Gancao Decoction (SGD) is a classic and representative oral administration of traditional Chinese medicine formula. It is composed of two Chinese herbal medicines, Paeoniae Radix Alba [Paeonia lactiflora Pall] and Glycyrrhizae Radix et Rhizoma. The clinical study found SGD could effectively reduce clinical symptoms and improve the level of inflammation in osteoarthritis (OA) patients. Purpose The aim of this study is to identify the efficacy and molecular mechanism of SGD in the treatment of OA, and find the new therapeutic target through RNA sequencing (RNA-Seq) to provide theoretical support for its clinical application. Methods Destabilization of the medial meniscus (DMM) OA rat model was established in vivo. Hematoxylineosin staining, safranin O/fast green staining and immunohistochemistry were used to observe changes of cartilage Histology and extracellular matrix (ECM) of cartilage cells. In vitro, the chondrocyte-like cells were derived from ATDC5 cells and induced by interleukin-1 beta to establish the model. The medial meniscotibial ligament (MTT) test was used to identify the effects of SGD on chondrocyte-like cell proliferation, and immunocytochemistry was used to assess changes in chondrocyte ECM. The differentially expressed genes (DEGs) were obtained by RNA-Seq. Meanwhile, the core targets were found through bioinformatics analysis, and then verified by qRT-PCR and Western Blotting. The inflammatory factors IL-1β, IL-6 and TNF-α were detected by ELISA. Results SGD could alleviate cartilage degeneration, and reduce ECM degradation in OA by upregulating COL2A1 and downregulating MMP-13. 120 key targets were screened from DEGs by RNA-Seq. Based on further bioinformatics analysis, interleukin 17 receptor B (IL-17RB), interleukin 23 receptor and growth differentiation factor 5 were finally selected as core targets. IL-17RB has rarely been reported in previous studies about OA, and worthy of further study. Subsequently, it was found that the gene and protein expressions of IL-17RB were significantly reversed in model group after SGD treatment. Moreover, SGD could inhibit the release of inflammatory factors by mediating IL-17RB in OA. Conclusions SGD reduced the release of inflammatory factors IL-1β, IL-6 and TNF-α, upregulated COL2A1 and downregulated MMP-13 to alleviate degradation of ECM, and reduced the cartilage degeneration and progression of OA by reducing IL-17RB in articular cartilage.